Linguistic Interviewing as a Method for Determining the Degree of Representativeness of Antonymous Pairs in the English Language - Lytvyn, Oksana (Lesya Ukrainka Eastern European National University, 2017)
In this article, the degree of representativeness of the examples (pairs of lexical units) which illustrate antonymous relations in the English language has been determined, utilizing the method of linguistic interviewing. The article presents the procedure and the results of the psycholinguistic experiment conducted. The peculiarities of the method of linguistic interviewing as a type of psycholinguistic experiment have been defined. A selection of antonymous pairs provided by leading linguists in the area of lexical semantics as illustrative examples in thirteen English-language linguistic works (monographs, textbooks and linguistic encyclopaedias) serves as the material for the experiment. All of the 101 respondents are scholars in the field of linguistics (Candidates (Ph.D.) and Doctors of Philological Sciences, as well as postgraduate students from the higher educational establishments of Ukraine), and are native speakers of Ukrainian, English being their first foreign language. In the experiment, the respondents were to identify which pairs of lexical items given in the list illustrate the relation of antonymy. After analyzing the results of linguistic interviewing, we were able to determine the pairs of antonyms with the highest and the lowest degrees of representativeness. The research demonstrated that gradable and complementary antonyms, mainly adjectives, have the highest degree of representativeness. In addition, we identified certain correlations with the results of linguistic interviewing conducted earlier, the respondents being linguistics scholars, including university and college professors, who are native speakers of English from five English-speaking countries. У статті виявлено міру репрезентативності прикладів (пар лексичних одиниць), які ілюструють антонімічні відношення в англійській мові, використовуючи метод лінгвістичного інтерв’ювання. Окреслено процедуру й результати проведеного психолінгвістичного експерименту. Схарактеризовано специфіку методу лінгвістичного інтерв’ювання як різновиду психолінгвістичного експерименту. Матеріалом для експерименту слугують антонімічні пари, подані провідними лінгвістами в сфері лексичної семантики як ілюстративні приклади в тринадцяти англомовних лінгвістичних працях (монографіях, навчальних посібниках і лінгвістичних енциклопедіях). Респондентами в експерименті є 101 лінгвіст-германіст, які є носіями української мови (кандидати й доктори філологічних наук, а також аспіранти з вищих навчальних закладів України). В експерименті респондентам треба було розпізнати, які пари лексичних одиниць, подані в списку, ілюструють відношення антонімії. У результаті лінгвістичного інтерв’ювання виявлено пари антонімів, які мають найвищу та найнижчу міру репрезентативності. Дослідження показало, що найвищу міру репрезентативності мають градуальні та комплементарні антоніми, які є переважно прикметниками. Крім того, виявлено значні кореляції з результатами лінгвістичного інтерв’ювання, у якому респондентами виступили лінгвісти (наукові співробітники, викладачі університетів та коледжів), носії англійської мови з п’яти англомовних країн.
Keywords: psycholinguistic experiment; linguistic interviewing; degree of representativeness; lexico-semantic category; antonymy; antonymous pair; психолінгвістичний експеримент; лінгвістичне інтерв’ювання; міра репрезентативності; лексико-семантична категорія; антонімія; антонімічна пара